Pelatihan Unit Kegiatan Mahasiswa Bola Voli Untuk Prestasi Mahasiswa Di Universitas - Ratno Susanto; Erwin S. Neolaka; Jurdan Martin Siahaan (ABHIPRAYA: Jurnal Pengabdian Masyarakat Kesehatan dan Sains, 2025)
In an attempt to foster success in the realm of sports, the Volleyball UKM training activity seeks to enhance students' technical, physical, and mental skills. At Nusa Cendana University, the Student Activity Unit (UKM) serves as a platform for extracurricular learning that fosters the growth of students' potential and overall character. The Volleyball UKM's inadequately designed and long-lasting training program is the present issue, which contributes to the team's lack of success in different competition events. Through the phases of need identification, training module preparation, routine training implementation, assessment, and mentoring, this community service project was executed through a participatory approach. The activity's outcomes demonstrated that UKM members' technical skills and game strategies improved, and their involvement in both internal and external competitions grew as well. It is anticipated that this program will establish itself as a model for long-term training that may generate exceptional students and enhance Nusa Cendana University's reputation in the sports industry